P16 Identifying partial anomalous pulmonary venous drainage (PAPVD) in patients presenting with suspected pulmonary hypertension (PH). (December 2018) - Lewis, R; Billings, C; Johns, C; Hurdman, J; Hamilton, N; Elliot, C; Charalampopoulos, A; Sabroe, I; Wild, J; Swift, A; Kiely, D; Condliffe, R
Abstract : Introduction: There are few published data regarding patients with PH and PAPVD. Aims: To review all patients seen at a large PH referral centre with suspected PH, in whom PAPVD was identified. Methods: Hospital databases were interrogated to identify all patients with PAPVD seen between 2007 and 2017. Baseline demographics, haemodynamics and radiological investigations were recorded. Results: Ninety-two patients with PAPVD were identified. Clinical characteristics are shown in the table 1. 79% were not previously known to have PAPVD, while 54% had isolated PAPVD. All cases of PAPVD were identified at CTPA or cardiac MRI while 33% of patients not previously known to have PAPVD also had an atrial septal defect visible on cross-sectional radiology. Of the 50 patients with isolated PAPVD, 47 underwent right heart catheterisation (RHC), mean values: mean pulmonary arterial pressure (mPAP) 36.5 (±15) mmHg, pulmonary arterial wedge pressure (PAWP) 14.2 (±6.9) mmHg, cardiac output 5.8 (±2) l/min, pulmonary vascular resistance 4.35 (±3.64) Woods Units. Qp:Qs analysis for intra-cardiac shunt – assessed by cardiac MR (performed in 24/50) was 1.53:1 (±0.49). Additional possible triggers for PH were present in 50% of those with isolated PAPVD: 14% emphysema on CT, 6% interstitial lung disease on CT, 4% portal hypertension, 18% possible left heart disease (elevated PAWP) and 8% chronic thromboembolic disease. Conclusions: The presence of PAPVD should be considered in patients with suspected PH and pulmonary venous anatomy should be specifically assessed on cross-sectional imaging. Approximately half of all patients with isolated PAPVD at a large PH referral centre had other possible triggers for the development of PH.